From the Manual of Ignacy Łukasiewicz - Krzysztof Andrzej Koniewicz; Monika Urbanik (Polish Pharmaceutical Society, 2022)
This year, we celebrate the 200th birthday of Ignacy Łukasiewicz (1822-1882), a pharmacist, revolutionary and independence activist, the founder of the world's first oil field, a pioneer of the petroleum industry in Europe, the inventor of the kerosene lamp introduced in 1853. Before his invention became known to the public and before he entirely devoted his occupational activity to the petroleum industry, Ignacy Łukasiewicz had been a long-time employee at a pharmacy. The collection of valuable memorabilia relating to Ignacy Łukasiewicz and held at the Jagiellonian University's Museum of Pharmacy contains a manuscript of apothecary manual. An analysis of the manual, authored to a considerable extent by Ignacy Łukasiewicz, leads to a highly interesting picture of therapy administered in the second half of the 19th century. The diversified nature of formulae contained in the manuscript indicates the versatile role played by the then pharmacies. The predominant forms of medicinal drugs recorded in the manual include tinctures, balsams, ointments, syrups, elixirs while rotulae, morsuli and electuaria represent ancient medication forms. The records include formulae for a variety of pharmaceutical preparations administered to cure sexually transmitted diseases, epidemics, formulae for mysterious drugs and miraculous medicines usually omitted in official pharmacopoeias but popular among patients. A large group of formulae contained in the manual is formed by various types of preparations that are conventionally classified in the Pars technica category. Examples include formulae for inks, blacks and shoe polishes, putty for porcelain repair, sealing wax, paints in a variety of colours, parquet lacquers, varnishes and colourful Bengal lights. The manual also contains a curiosity: a large chapter containing recipes for various types of liqueurs and vodkas as well as recipes for preserved food. The apothecary manual also contains cosmetic formulations - for such products as hair dyes, pomades, eau de Cologne, perfumes. A separate chapter is dedicated to methods used to treat poisoning e.g. by arsenic trioxide, copper, lead, baryte, ergot fungi or mushrooms as well as recommended conduct after being bitten by venomous animals.